2009
DOI: 10.1111/j.1439-0396.2008.00827.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of field bean (Vicia faba L. var. minor) dietary supplementation on plasma thyroid hormones, insulin, insulin‐like growth factor‐1 concentrations and mohair characteristics in growing Angora goat kids

Abstract: Twenty-two Angora kids were used to study the effect of a dietary supplementation with field bean (Vicia faba L. var. minor) on hair follicle activity, mohair characteristics and plasma total thyroxine (T4), triiodothyronine (T3), insulin (INS) and insulin-like growth factor-1 (IGF-1) concentrations. At birth, their mothers were divided in two groups (S: supplemented, C: control), the S group being supplemented with 300 g/head/day of whole field bean. At weaning, diet of kids from S group was supplemented with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 59 publications
1
3
0
Order By: Relevance
“…As a matter of fact, it has been reported that there is a negative correlation between IGF-1 concentrations and body mass in 36 mammalian species, and that high IGF-1 levels allow for cancer growth and thus shorten the animal's life span (Stuart and Page, 2010). However, this result contrasts with the reported negative correlations (r = −0.56) between IGF-1 concentrations and live weight in Angora goat kids (Acuti et al, 2009). In summary, the findings obtained from this study are generally compatible with studies on other mammalian species.…”
Section: Discussionsupporting
confidence: 54%
“…As a matter of fact, it has been reported that there is a negative correlation between IGF-1 concentrations and body mass in 36 mammalian species, and that high IGF-1 levels allow for cancer growth and thus shorten the animal's life span (Stuart and Page, 2010). However, this result contrasts with the reported negative correlations (r = −0.56) between IGF-1 concentrations and live weight in Angora goat kids (Acuti et al, 2009). In summary, the findings obtained from this study are generally compatible with studies on other mammalian species.…”
Section: Discussionsupporting
confidence: 54%
“…Nutritional changes affect plasma concentrations of insulin, growth hormone (GH), 3, 5, 3' triiodotironine (T 3 ), thyroxine (T 4 ) and metabolites such as glucose, ammonia nitrogen (N-NH 3 ) and volatile fatty acid (VFA) (Gerrits et al, 1998;Todini et al, 2007a, b;Acuti et al, 2009). Changes in nutrition are closely associated to growth.…”
Section: Introductionmentioning
confidence: 99%
“…[ 10 ] in Honamlı and native hair goats in Turkey, in which it increased with age, and the concentration at 4 months was lower than those measured at 8 and 12 months. However, in growing Angola goat kids, circulating IGF-1 decreased from 12 to 22 weeks of age [ 11 ]. Two studies in goats showed that plasma IGF-1 levels in kids after birth were elevated until approximately 4 months of age and declined without significance thereafter [ 5 , 12 ].…”
Section: Discussionmentioning
confidence: 99%